2014
DOI: 10.1007/s00256-014-2079-z
|View full text |Cite
|
Sign up to set email alerts
|

Repair of distal biceps brachii tendon assessed with 3-T magnetic resonance imaging and correlation with functional outcome

Abstract: The quality of functional outcome after anatomical elbow rehabilitation of DBT correlates with the extent of tendinous hypertrophy during the healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…4,7,14 Fixation methods for anatomic repair include intraosseous Endo-Buttons, transosseous reinsertion suture anchors, interference screws, and transosseous sutures. 1,13,16 Given that our study has shown that the majority of DBTs exit the muscle belly as 2 discrete tendons and given that it appears that these tendons may have distinct insertions on the radial tuberosity to perform the 2 primary actions of the biceps, it is perhaps unsurprising that anatomic ''footprint'' repairs lead to better functional outcomes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…4,7,14 Fixation methods for anatomic repair include intraosseous Endo-Buttons, transosseous reinsertion suture anchors, interference screws, and transosseous sutures. 1,13,16 Given that our study has shown that the majority of DBTs exit the muscle belly as 2 discrete tendons and given that it appears that these tendons may have distinct insertions on the radial tuberosity to perform the 2 primary actions of the biceps, it is perhaps unsurprising that anatomic ''footprint'' repairs lead to better functional outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…On the basis of the current literature, operative fixation of DBT tears is generally recommended given the potential for poor long-term functional outcomes in conservatively managed cases. 13 Nonanatomic repairs are now usually limited primarily to older patients and cases of delayed repair, 1 whereas anatomic repairs, using either intraosseous EndoButtons (Smith & Nephew Endoscopy, Andover, MA), transosseous reinsertion suture anchors, interference screws, or transosseous sutures, 1,13,16 have become standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterotopic ossifications are readily visualized on radiographs or by CT. To properly visualize the repaired distal biceps tendon directly, MRI is the best modality to exclude a tendon retear. 37 To achieve this goal, the elbow should be scanned in the so-called FABS position (i.e., elbow flexed, abducted, and supinated). 38 Moreover, peritendinous soft tissue abnormalities, such as postoperative bursitis, septic complications, or granulation tissue excess within the surgical tunnel, are all detectable by MRI ( Fig.…”
Section: Typical Postoperative Situations and Complications With Elbo...mentioning
confidence: 99%